DNA repair- and nucleotide metabolism-related genes exhibit differential CHG methylation patterns in natural and synthetic polyploids (Brassica napus L.). (1st July 2021) - Yin, Liqin; Zhu, Zhendong; Huang, Liangjun; Luo, Xuan; Li, Yun; Xiao, Chaowen; Yang, Jin; Wang, Jisheng; Zou, Qiong; Tao, Lanrong; Kang, Zeming; Tang, Rong; et al.
Abstract: Polyploidization plays a crucial role in the evolution of angiosperm species. Almost all newly formed polyploids encounter genetic or epigenetic instabilities. However, the molecular mechanisms contributing to genomic instability in synthetic polyploids have not been clearly elucidated. Here, we performed a comprehensive transcriptomic and methylomic analysis of natural and synthetic polyploid rapeseeds ( Brassica napus ). Our results showed that the CHG methylation levels of synthetic rapeseed in different genomic contexts (genes, transposon regions, and repeat regions) were significantly lower than those of natural rapeseed. The total number and length of CHG-DMRs between natural and synthetic polyploids were much greater than those of CG-DMRs and CHH-DMRs, and the genes overlapping with these CHG-DMRs were significantly enriched in DNA damage repair and nucleotide metabolism pathways. These results indicated that CHG methylation may be more sensitive than CG and CHH methylation in regulating the stability of the polyploid genome of B. napus . In addition, many genes involved in DNA damage repair, nucleotide metabolism, and cell cycle control were significantly differentially expressed between natural and synthetic rapeseeds. Our results highlight that the genes related to DNA repair and nucleotide metabolism display differential CHG methylation patterns between natural and synthetic polyploids and reveal the potential connection between the genomic instability of polyploid plants with DNA methylation defects and dysregulation of the DNA repair system. In addition, it was found that the maintenance of CHG methylation in B. napus might be partially regulated by MET1 . Our study provides novel insights into the establishment and evolution of polyploid plants and offers a potential idea for improving the genomic stability of newly formed Brassica polyploids.